Exopolysaccharide is required for motility, stress tolerance, and plant colonization by the endophytic bacterium Paraburkholderia phytofirmans PsJN - Fu, Benzhong; Yan, Qing (Frontiers in Microbiology, 2023)
Paraburkholderia phytofirmans PsJN is an endophytic bacterium and has been shown to promote the growth and health of many different plants. Exopolysaccharide (EPS) plays important roles in plant-bacteria interaction and tolerance to environmental stresses. However, the function of EPS in PsJN and its interaction with plant remain largely unknown. In this study, a deletion mutation of bceQ gene, encoding a putative flippase for the EPS biosynthesis, was introduced in the genome of PsJN. The ΔbceQ mutant produced a significantly lower level of EPS than the wild type strain in culture media. Compared to the wild type PsJN, the ΔbceQ mutant was more sensitive to desiccation, UV damage, salt (NaCl) and iron (FeCl3) stresses and bacteriophage infection. More importantly, the mutation of bceQ decreased the endophytic colonization of PsJN in camelina (Camelina sativa) and pea (Camelina sativa) under plant drought stress condition. To the best of our knowledge, this is the first report that EPS production is required for the maximal colonization of an endophytic bacterium in the plant tissues under stress conditions.